Our Experience and Literature Update Regarding Concomitant Radiotherapy with CDK4/6 Inhibitors and Hormonal Therapy in Metastatic Breast Cancer - Laura-Florentina Rebegea; Dorel Firescu; Oana-Gabriela Trifanescu; Roxana-Andreea Rahnea-Nita; Liviu Bilteanu; Mihaela Dumitru; Florentina Lacatus; Gabriela Rahnea-Nita (Journal of Mind and Medical Sciences)
Background and Objectives: Standard treatment in metastatic breast cancer with positive estrogen receptors and negative HER2neu is represented by CDK4 inhibitors combined with aromatase inhibitors or fulvestrant. Palliative radiotherapy is indicated for symptoms or local–regional control. Multiple preclinical data suggest a potential synergistic effect when CDK4/6 inhibitors and radiotherapy are administered concurrently. We are trying to address some questions and/or to establish correlations within a subgroup of patients with unusual toxicities, the safety of combined treatments, the correlation with radiotherapy techniques and fractionation schemas. Also, we are aware that some organs at risk of a rapid turnover are more vulnerable to the occurrence of acute toxicities. Materials and Methods: This retrospective study includes 20 patients with metastatic breast cancer, treated with CDK4 inhibitors and radiotherapy on 29 disease sites; we followed the compliance and toxicities of combined treatments. Results: Regarding the recorded hematological toxicities, grade 1 associated with CDK4 inhibitors, occurring anterior radiotherapy was recorded; grade 2, leucopenia during radiotherapy presented in three cases without radiotherapy interrupting and leucopenia with neutropenia grade 3 presented in one case after pleural secondary lesion’s irradiation. Non-hematological grade 3 toxicities occurred in two cases: one case with grade 3 enteritis, at 2 weeks from bone metastases irradiation—iliac bone (in field toxicity) and one case with radiodermitis during radiotherapy on the breast and lymph node level, in the second week of external radiotherapy (RTE). Conclusions: In all analyzed cases, we obtained control of irradiated lesions. Secondary toxicities occurred only in irradiated areas. A close monitoring of patients during combined treatment must be considered and we are confident that in the future it will be possible to identify the subgroup of patients with a high risk of unusual toxicities occurring; additionally, we hope that using more conforming radiotherapy techniques minimizes the organ being at risk from radiation doses.